Onset, duration and unresolved symptoms, including smell and taste changes, in mild COVID-19 infection: a cohort study in Israeli patients. (May 2021) - Klein, Hadar; Asseo, Kim; Karni, Noam; Benjamini, Yuval; Nir-Paz, Ran; Muszkat, Mordechai; Israel, Sarah; Niv, Masha Y.
Abstract: Objectives: To characterize longitudinal symptoms of mild coronavirus disease 2019 (COVID-19) patients for a period of 6 months, to potentially aid in disease management. Methods: Phone interviews were conducted with 103 patients with mild COVID-19 in Israel over a 6-month period (April 2020 to October 2020). Patients were recruited via social media and word to mouth and were interviewed up to 4 times, depending on reports of their unresolved symptoms. Inclusion criteria required participants to be residents of Israel aged 18 years or older, with positive COVID-19 real-time PCR results and nonsevere symptoms. The onset, duration, severity and resolution of symptoms were analysed. Results: A total of 44% (45/103), 41% (42/103), 39% (40/103) and 38% (39/103) of patients experienced headache, fever, muscle ache and dry cough as the first symptom respectively. Smell and taste changes were experienced at 3.9 ± 5.4 and 4.6 ± 5.7 days (mean ± standard deviation (SD)) after disease onset respectively. Among prevalent symptoms, fever had the shortest duration (5.8 ± 8.6 days), and taste and smell changes were the longest-lasting symptoms (17.2 ± 17.6 and 18.9 ± 19.7 days; durations censored at 60 days). Longer recovery of the sense of smell correlated with the extent of smell change. At the 6-month follow-up, 46% (47/103) of the patients had at least one unresolved symptom, most commonly fatigue (22%, 23/103), smell and taste changes (15%, 15/103 and 8%, 8/103 respectively) and breathing difficulties (8%, 8/103). Conclusions: Long-lasting effects of mild COVID-19 manifested in almost half of the participants reporting at least one unresolved symptom after 6 months. Graphical abstract: Image 1